Factors related to the survival of patients who start receiving hemodialysis. Institute of Nephrology - Jose Antonio Alvarez Ramírez; Daneysis Santiesteban Miranda; Francisco Gutiérrez García (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Chronic kidney disease is a health problem because of its impact on individuals, society and the economy. There is not enough knowledge of the factors related to survival in patients who start hemodialysis in our environment. Objective: To identify the factors related to the survival of patients who started receiving hemodialysis. Material and Methods: A descriptive retrospective study was conducted in 81 patients who started receiving hemodialysis in the "Dr. Abelardo Buch" Institute of Nephrology in the period between January 1, 2011 and December 31, 2016. Sociodemographic and clinical variables were analyzed. A correlation between these variables and survival was made. The level of significance in all the tests performed was determined to be ɑ= 0.05.   Results: A total of 81 patients were studied.  The mean age was 55 years. The male sex (61,7%) and the white race (59,3 %) predominated in the study.  The statistically significant variables were malnutrition (body mass index < 18.5 kg/m2) with a median survival of (7,6+-4,9; log rank: 0,015), serum albumin levels lower than 35 g/L, with (33.1 +-5.4; log rank: 0.050), lack of previous nephrological follow-up, with (21,5 +-2,6; log rank: 0,041) and the use of central venous catheter as vascular access with (32,4+-3,5; log rank: 0,038). Conclusions: Malnutrition, hypoalbuminemia, the use of central venous catheter as vascular access and previous nephrological follow-up negatively affected the survival of patients on hemodialysis.